FEATURES OF THE SELECTION OF WEAPONS FOR THE DECORATION OF HISTORICAL INTERIORS OF CASTLES AND PALACES - Okonchenko, Olha; Okonchenko, Іgor (Theory and practice of design, 2022)
Today, the process of museumification and adaptation of monuments of defense and residence architecture for exposition, cultural and artistic, and cultural and educational functions continues. The development of conceptual design for the historic interiors of these buildings actualizes the need to use weapons in the context of demonstrating compositions (military fittings] as components of the artistic image associated with the function and history of these cultural heritage sites. The article’s purpose is to highlight the impact factors on the quality of the artistic image of military compositions in the interior, to present the general principles of creating compositions from weapons, and to justify the choice of weapon analogs for creating replicas on the example of the Hetman’s Hall of the Zhovkva Castle. The research is based on the use of historical method to study the sources for the storage of weapons in the past in the interiors of castles and palaces; typological method and comparative analysis to select analogs for the creation of replicas; artistic, stylistic and graphic method to build compositional schemes. The article highlights the main factors impacting the artistic and image quality of military compositions in the interior; we developed several simple layout schemes that can be used as a basis for creating compositions of weapons elements for placement in the interiors of defensive and residence architecture; we characterized the types of weapons (halberd, mace, hatchet hammer, flanged mace, partisan, spear, ax hammer, saber], which due to their external characteristics and attractiveness are perfect for creating replicas or models (as design elements in the creation of military compositions]. The above-mentioned types of weapons were widespread in the 16 – 17 centuries on the territory of Central and Eastern Europe and Ukraine, in particular, and are placed in many museum collections of Ukraine and Poland and in private collections, which greatly simplifies the selection of analogs for making copies (replicas]. The experience of our study can be used to develop the design of museum premises based on castles, palaces, fortresses, etc., where, according to the plan, it is necessary to connect the interior design with their residential or military past.